Hình:
Giải:
+ Ta có: \(\widehat{yOn}< \widehat{xOy}\left(50^0< 180^0\right)\)
Ta có đẳng thức:
\(\widehat{yOn}+\widehat{xOn}=\widehat{xOy}\)
Hay \(50^0+\widehat{xOn}=180^0\)
\(\Leftrightarrow\widehat{xOn}=180^0-50^0=130^0\)
+ Ta có: \(\widehat{xOm}< \widehat{xOy}\left(150^0< 180^0\right)\)
Ta có đẳng thức:
\(\widehat{xOm}+\widehat{yOm}=\widehat{xOy}\)
Hay \(150^0+\widehat{yOm}=180^0\)
\(\Leftrightarrow\widehat{yOm}=180^0-150^0=30^0\)
+ Ta có: \(\widehat{yOm}< \widehat{yOn}\left(30^0< 50^0\right)\)
Ta có đẳng thức:
\(\widehat{yOm}+\widehat{mOn}=\widehat{yOn}\)
Hay \(30^0+\widehat{mOn}=50^0\)
\(\Leftrightarrow\widehat{mOn}=50^0-30^0=20^0\)
Vậy ...